PENDIDIKAN KARAKTER DI PONDOK PESANTREN SALAFIYAH - Latipah, Euis; Suhartini, Andewi; Ahmad EQ, Nurwadjah (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Pesantren becomes an Islamic educational institution that is in demand by many people in hopes of shaping one's character. One of the models of pesantren huts in Indonesia is Salafiyah pesantren. Pesantren Salafiyah is a pesantren that has its own characteristics. Kiai directly taught in front of the students with a focus on the study of classical books or yellow books. The pattern of education has taken root in some people in Indonesia. Character education is strongly instilled through specific specific patterns of messaging. The success of character education is influenced by the example or figurity of a kiai, is implementative in daily activities so as to form a pattern of habituation and attached strongly to the santri self in forming character.